2011
DOI: 10.1093/infdis/jiq152
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Interpretation of the RV144 HIV Vaccine Efficacy Trial in Thailand: A Case Study for Statistical Issues in Efficacy Trials

Abstract: Recently, the RV144 randomized, double-blind, efficacy trial in Thailand reported that a prime-boost human immunodeficiency virus (HIV) vaccine regimen conferred ∼30% protection against HIV acquisition. However, different analyses seemed to give conflicting results, and a heated debate ensued as scientists and the broader public struggled with their interpretation. The lack of accounting for statistical principles helped flame the debate, and we leverage these principles to provide a more scientific interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…112,113 The prime-boost vaccine regimen consisted of a recombinant canarypox vector, ALVAC-HIV (vCP1521) prime and AIDSVAX B/E boost. The vaccine regimen was safe and generally well tolerated.…”
Section: Hiv Vaccine Clinical Developmentmentioning
confidence: 99%
“…112,113 The prime-boost vaccine regimen consisted of a recombinant canarypox vector, ALVAC-HIV (vCP1521) prime and AIDSVAX B/E boost. The vaccine regimen was safe and generally well tolerated.…”
Section: Hiv Vaccine Clinical Developmentmentioning
confidence: 99%
“…Of these four trials, only the RV144 trial, the largest HIV vaccine trial so far concluded in humans, showed a limited but significant protection (31.2%) from HIV acquisition (P ϭ 0.04) in the 16,395 participants (4,5). This result has engendered cautious optimism about the feasibility of a vaccine for HIV.…”
mentioning
confidence: 99%
“…This study, known as RV144, conducted by the US military research program in collaboration with several Thai institutions in more than 16,000 Thai associate with any particular danger in advance of HIV [64][65][66]. The system consists of a canarypox vector Prime Minister recombinant vaccine (ALVAC HIV, and Sanofi Pasteur) and boost the protein gp120 (AIDSVAX B/E, Global Solutions for Infectious Diseases).…”
Section: Step Studymentioning
confidence: 99%